Production of biodegradable package material from tofu industry byproduct. Issue 1 (April 2020) - Antonius, R; Simamora, L L B; Setiani, P; Sitorus, T A; Luthfiyana, H; Idris, Z Y
Abstract: Plastic has been widely used as single-use package and carrier material due to its low price, strength, practicality, and versatility. On the other hand, plastic requires a long period to naturally decompose. Nowadays, a huge number of plastic wastes have caused detrimental impacts to the global environment, hence a more environmentally benign substance of making plastic is a significant importance. This study proposed the production of biodegradable material from nata de soya, which is composed from whey waste using melt intercalation method. This environmentally-friendly substance was mainly obtained from tofu industry byproduct which is known as 'whey', through fermentation process using Acetobacter xylinum bacteria. Melt intercalation method was used to obtain desired texture and characteristic, the step was the fermented product mixed with chitosan, acetic acid, glycerol, and tapioca starch, with various range of concentration. The mixed component then underwent milling and drying process for finalization. As for characteristic of the materials, tested parameters include solubility, water resistance, and biodegradability in the environment. Our results showed the potential of this material to substitute the use of plastic and is applicable for versatile purposes. Water resistance was up to 95 minutes, and the material was able to be completely degraded in around 60 days.